Indoor building fuzzy control of energy and comfort management - Shaikh, P.H. (Maxwell Science Publications, 2013)
This study reports the fuzzy inference system controllers. They are employed in order to control actuator systems for thermal, visual and indoor air quality power consumption. The implementation of the Fuzzy Logic Control (FLC) system, allows an stochastic interval range of comfort index as susceptible to human body, achieving numerous power demand values for the actuator operations. The potential benefit of the automated smart building are high-level comfort, improved device efficiency, environment friendliness and reduced energy consumption as well as cost. The simulation results are shown describing the behavourial relation for each control parameter with the power consumption. Â© Maxwell Scientific Organization, 2013.